Prenatal PCB and Dioxin and Cognitive Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effects of environmental exposure to polychlorinated biphenyls (PCB) and dioxins on cognitive abilities in Dutch children at 42 months of age were assessed at the Sophia Children's Hospital, Rotterdam, The Netherlands.